Eight steps’ paradigm shift in men’s 110 metres hurdles: an 89 years retrospective study - Pinho, João Pedro (2017)
Men’s 110 metres hurdles is one of the oldest disciplines in the Olympic Games and yet scarce anecdotal reports are found to pinpoint technical elements indicators of success. The approach technique to the hurdles has been raised by coaches as a potential element of success however it seems that the approach strategies undertaken to the first hurdle have not been investigated to the current date. Therefore, this study aimed to examine the employment of the seven and eight steps strategy until the first hurdle in the 110 m discipline among the Olympic Games and World Championships in Athletics’ finalists. Public domain videos of the events in the period between 1924 and 2013 were assessed. An international level sprint and hurdles’ coach, using the Dartfish software, assessed the number of steps taken until the first hurdle. A left-tailed one sample sign test showed that although the seven steps strategy adoption seems to have begun in 1960 it was only in 2011 that it was considered a dominant tactic. Due to determination of factors that influence the choice of strategy or their respective influence on performance falling outside the scope of this study, future research is needed in this area. Notwithstanding, the success by the hurdlers that adopt the seven steps strategy, evidenced by the number of medals won, allowed to pinpoint the approach strategy to the first hurdle as a potential performance variable to be investigated.